Human T-lymphotropic virus type 1 infection and disease in Spain. (31st July 2017) - de Mendoza, Carmen; Caballero, Estrella; Aguilera, Antonio; Requena, Silvia; de Lejarazu, Raúl Ortiz; Pirón, María; González, Rocío; Jiménez, Ana; Roc, Lourdes; Treviño, Ana; Benito, Rafael; Fernández-Alonso, Miriam; et al.
Abstract : N/A: Human T-lymphotropic virus type 1 (HTLV-1) infection is a neglected disease despite roughly 15 million people are chronically infected worldwide. Lifelong less than 10% of carriers develop life-threatening diseases, mostly a subacute myelopathy known as tropical spastic paraparesis (TSP) and a lymphoproliferative disorder named adult T-cell leukemia (ATL). HTLV-1 is efficiently transmitted perinatally (breastfeeding), sexually (more from men to women) and parenterally (transfusions, injection drug user (IDU), and transplants). To date there is neither prophylactic vaccine nor effective antiviral therapy. A total of 327 cases of HTLV-1 infection had been reported at the HTLV-1 Spanish registry until December 2016, of whom 34 had been diagnosed with TSP and 25 with ATL. Overall 62% were Latin American immigrants and 13% were persons of African origin. The incidence of HTLV-1 in Spain has remained stable for nearly a decade with 20–25 new cases yearly. Of the 21 newly diagnosed HTLV-1 cases during year 2016, one was a native Spaniard pregnant woman, and four presented with symptomatic disease, including three with ATL and one with TSP. Underdiagnosis of HTLV-1 in Spain must be high (iceberg model), which may account for the disproportionate high rate of symptomatic cases (almost 20%) and the late recognition of preventable HTLV-1 transmissions in special populations, such as newborns and transplant recipients. Our current estimate is of 10 000 persons living with HTLV-1 infection in Spain. Given the large flux of immigrants and visitors from HTLV-1 endemic regions to Spain, the expansion of HTLV-1 screening policies is warranted. At this time, it seems worth recommending HTLV testing to all donor/recipient organ transplants and pregnant women regardless place of birth. Although current leukoreduction procedures largely prevent HTLV-1 transmission by blood transfusions, HTLV testing of all first-time donors should be cost-effective contributing to unveil asymptomatic unaware HTLV-1 carriers.